The relationship between physical activity and quality of life of people in age 25–30, 35–40 and 45-50 - Krajewska, Małgorzata; Galijewska, Katarzyna; Krajewski, Stanisław; Kucharczuk-Kopycińska, Magda (Journal of Education, Health and Sport, 2016)
Purpose: The aim of the research was to assess the relationship between physical activity and quality of life of the respondents. Methods: There was a study conducted on 150 people divided into three age groups: 25-30, 35-40 and 45-50 years old. The study was conducted by using its own questionnaire. The evaluated factors were health status, material status, life satisfaction, attitudes to drugs and drug use, ways of spending free time, the ratio of physical activity or cultivated forms of activity. In order to carry out the correlation analysis between the subjective assessment of quality of life and physical activity there were numerical indicators of quality of life and physical activity introduced. Results: The correlation between these indicators for all examined and for different age groups was assessed. The most evident correlation appeared in the oldest group. Conclusions: The examined are aware that taking up physical activity regularly is conducive to improving their well-being, physical condition and appearance. The subjective evaluation of the level of general fitness and the frequency of doing physical activity tend to fall with age. Physical activity influences not only the physical and psychological health, but also indirectly conditions the capability of succeeding in other areas of life.